2023
DOI: 10.9755/ejfa.2022.v34.i12.2964
|View full text |Cite
|
Sign up to set email alerts
|

Determination of the factors affecting red meat consumption in türkiye with the two-stage Heckman model

Abstract: Red meat consumption in the world is in a rapid upward trend and has reached a level that involves many sectors. Studies on red meatconsumption have become a guide not only for policies for the red meat sector, but also for health and environmental practices. Withits population size, structure and economy among emerging economies, Türkiye has an important place in red meat consumption. In thepresent study, red meat consumption in Türkiye and the factors affecting the amount of consumption were examined with th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 26 publications
(31 reference statements)
0
1
0
Order By: Relevance
“…However, it was found that there was no significant difference in camel meat consumption between less or non-educated households and more educated households. Ayyıldız and Çiçek (2022) found that no significant relationship between the likelihood of consuming red meat and the level of education of the head of household. According to analysis results, it was found that there was no significant difference in camel meat consumption between married individuals and non-married individuals.…”
Section: Frequencies Resultsmentioning
confidence: 91%
“…However, it was found that there was no significant difference in camel meat consumption between less or non-educated households and more educated households. Ayyıldız and Çiçek (2022) found that no significant relationship between the likelihood of consuming red meat and the level of education of the head of household. According to analysis results, it was found that there was no significant difference in camel meat consumption between married individuals and non-married individuals.…”
Section: Frequencies Resultsmentioning
confidence: 91%